Structural Adjustment and Soil Degration in Tanzania: A CGE-model Approach with Endogenous Soil Productivity - Jens Aune; Solveig Glomsrød; Vegard Iversen; Henrik Wiig (Statistics Norway, Research Department, 1997)
In this paper, a model of the nitrogen cycle in the soil is incorporated in a Computable General Equilibrium (CGE) model of the Tanzanian economy, thus establishing a two way link between the environment and the economy. For a given level of natural soil productivity, profit maximising farmers choose a production technique and the optimal production volume, which in turn influences the soil productivity the following years through the recycling of nitrogen from the residues of roots and stover and the degree of erosion. The model is used to simulate the effects of typical structural adjustment policies: a reduction in agro-chemicals subsidies, reduced implicit export tax rate, a devaluation of the currency, a cut in governmental expenditure and a reduction of foreign transfers. The result of a joint implementation is a 9 percent higher GDP level compared to the baseline scenario after 10 years. The effect of soil degradation is found to represent a reduction in the GDP level of more than 5 percent for the same time period.
Keywords: C68; Q16; Q24; 330; CGE-model; soil degradation; economic growth; structural adjustment